In Death's Waiting Room Living and Dying with Dementia in a Multicultural Society - The, Anne-Mei (Care & Welfare, 2008)
In Death's Waiting Room is a penetrating story about people suffering from dementia in a multi-cultural society, relevant to us all. Anne-Mei The carried out two years of ethnographic research in a nursing home in the Netherlands revealing what usually remains hidden from the public: the decision to stop treatment, the cultural and social gap between the Dutch occupants and the black Caribbean nursing staff, the communication problems with relatives, the tensions and aggression. But she also shares with us the touching and funny moments and experiences with the elderly occupants. This book also unravels "the Blauwborgje case" - which was the focus of much media attention in the Netherlands in the late 1990s - in which a nursing home refused to re-hydrate a man with extreme dementia because they considered his condition to be terminal, whilst his family disagreed and pressed charges for attempted murder. Anne-Mei The gives an account of the events that took place and also explores the wider relevance of the case.